Web-Based Interfaces for Virtual C. elegans Neuron Model Definition, Network Configuration, Behavioral Experiment Definition and Experiment Results Visualization - Epelde, Gorka; Morgan, Fearghal; Mujika, Andoni; Callaly, Frank; Leškovský, Peter; McGinley, Brian; Álvarez, Roberto; Blau, Axel; Krewer, Finn (Frontiers in Neuroinformatics, 2018)
The Si elegans platform targets the complete virtualization of the nematode Caenorhabditis elegans, and its environment. This paper presents a suite of unified web-based Graphical User Interfaces (GUIs) as the main user interaction point, and discusses their underlying technologies and methods. The user-friendly features of this tool suite enable users to graphically create neuron and network models, and behavioural experiments, without requiring knowledge of domain-specific computer-science tools. The framework furthermore allows the graphical visualisation of all simulation results using a worm locomotion and neural activity viewer. Models, experiment definitions and results can be exported in a machine-readable format, thereby facilitating reproducible and cross-platform execution of in silico \cele experiments in other simulation environments. This is made possible by a novel XML-based behavioural experiment definition encoding format, a NeuroML XML-based model generation and network configuration description language, and their associated GUIs. User survey data confirms the platform usability and functionality, and provides insights into future directions for web-based simulation GUIs of C. elegans and other living organisms. The tool suite is available online to the scientific community and its source code has been made available.